Risk factors of survival after liver transplantation for HCC: a multivariate single-center analysis - Hoffmann, Katrin; Hinz, Ulf; Hillebrand, Norbert; Radeleff, Boris; Ganten, Tom M.; Schirmacher, Peter; Schmidt, Jan; Büchler, Markus W.; Schemmer, Peter (Clinical transplantation, 2011)
Hoffmann K, Hinz U, Hillebrand N, Radeleff BA, Ganten TM, Schirmacher P, Schmidt J, Büchler MW, Schemmer P. Risk factors of survival after liver transplantation for HCC: a multivariate single-center analysis. Clin Transplant 2011: 25: E541-E551. © 2011 John Wiley & Sons A/S. Abstract: Background: The selection criteria for liver transplantation (LT) in patients with hepatocellular cancer (HCC) are well defined. Increasing evidence suggests that the effectiveness of pre-transplant bridging influences the individual course after LT significantly. Thus, the aim of this study was to determine its impact on tumor progression during waiting time and identify patient subgroups with favorable oncological long-term outcome. Methods: Prospectively collected data of 78 consecutive patients undergoing LT for HCC between 2001 and 2007 were analyzed retrospectively. Survival rates were assessed using the Kaplan-Meier estimate. Clinicopathologic prognostic factors were identified by Cox regression analysis. Results: After 48.9 months of median follow-up, the five-yr overall survival rate is 57% with a five-yr recurrence-free survival rate of 74%. Progressive disease (PD) during bridging was developed in 32% of patients, and a trend toward impaired overall survival in patients with PD before LT was detected in multivariate analysis (p = 0.073). HCC ≥3 cm was associated with a three times increased risk of recurrent disease. Neither fulfillment of MILAN criteria nor bridging with transarterial chemoembolization had an impact on the outcome. Conclusion: PD during waiting time influences the oncological course after LT. However, even with an increasing organ shortage, further studies are warranted to define clear selection criteria based on the biological tumor behavior and allow a more personalized treatment.